(untitled) (Scientia Agropecuaria, 2020)
The research aimed to develop a children’s pumpkin compote, functional, inexpensive, preservative-free and of considerable shelf life. The effect of incorporating xanthan gum (XG) was evaluated at three concentrations (0.10%, 0.15% and 0.20%) on its rheological properties. Sensory characteristics were applied to 60 panelists (30 undergraduate students and 30 children between 2 and 3 years). Its physical, physicochemical, and microbiological characteristics were determined. With the pH values was estimated the shelf life of pumpkin compote using accelerated testing method. The product was stored at 20 °C, 30 °C and 40 °C for 0, 10, 20, and 30 days. The results show the pumpkin compote presented non-Newtonian behavior, pseudoplastic, and was adjusted to the Ostwald Waele model (R2 > 0.98). Compote formulated with 0.15% of XG was conceived as the best treatment, with a "Like" scale for color attributes, smell, texture, taste and general appearance (3.80 to 4.13 points) associated with the presence of 82.45% humidity, 5.40 pH, 17 °Brix, and absence of molds, yeasts and total coliforms. Influence of temperature on viscosity was modeled using Arrhenius equation, showing a decrease in viscosity with increasing temperature. Finally, the estimated shelf life at 20 °C, 30 °C and 40 °C were 125, 75, and 45 days, respectively.